Characterizing Abuse Progression of Immediate-Release Hydrocodone Combination Products. (July 2018) - Beaumont, Jared; Cassidy, Theresa A.; Oyedele, Natasha; Guenther, Sven; Mickle, Travis C.
This study examined patterns of hydrocodone combination product (HCP) abuse and their potential role in abuse progression of prescription opioids and other drugs. An Internet survey was administered to 472 adult opioid users in the United States who used HCPs nonmedically. Alternate routes (33%) and concomitant drug use (45%) were indicated more frequently during respondent's most recent HCP nonmedical use compared with their initial use (20% and 24%, respectively). Those initiating HCP nonmedical use during adolescence used alternate routes (e.g., chewing, snorting) throughout their lifetime more frequently (69.5%) compared with those older when initiating HCP nonmedical use (51.0%). A different abuse pattern was observed from first to most recent HCP use, starting with oral administration of intact tablets followed by use of alternate routes and concomitant use of illicit drugs, sometimes use of heroin. These data may inform future public health interventions, including the potential development of abuse-deterrent immediate-release opioids.